Fair Use and the New Transformative - Sites, Brian (The Columbia Journal of Law & the Arts, 2016)
In the eyes of many, the “transformative” subfactor of the fair use analysis is expanding. Recent decisions such as Cariou v. Prince, Seltzer v. Green Day, and the Google Books line of cases have allegedly pushed the doctrine into new and problematic territory. Given the subfactor’s power in the aggregate fair use analysis and its strong parallels to the goals of copyright law, the scope of the transformativeness inquiry is critical to defining permitted uses under § 107. Accordingly, this Article assesses the claims that Cariou et al. have modified the scope of transformativeness. Part I paints, in broad strokes, the history of the transformativeness subfactor. Part II focuses on recent copyright decisions and concludes that some cases have expanded the doctrine of transformativeness into new territory. Some of those modifications are inconsistent with prior decisions. Finally, Part III considers paths to stabilize the transformative subfactor.